Molecular epidemiology of hepatitis C virus genotypes in Bushehr province, Iran - Vahdat, K.; Keyvani, H.; Tabib, S.M.; Rostamabadi, S.; Valizadeh, S.M.; Cheraghi, S.; Shamsian, S.; Zandi, K. (Verduci Publisher, 2010)
Background and Objectives: Molecular epidemiology of hepatitis C virus (HCV) is very important for the treatment of hepatitis C infection. The aim of this study was to determine the distribution of HCV genotypes in Bushehr province (South West of Iran). Materials and Methods: A total of 100 patients who were detected as positive for HCV antibody (by using ELISA method and RIBA test) referred to Arya Virology Laboratory between 2007-2009 in order to molecular diagnosis and furthermore virus genotyping. After detection of HCV, RNA genotyping of virus was done by using genotype specific primers. Results: Genotype 1a was found in 49% of the patients and genotype 3a was found in 40% of the patients and 1b in 5% of patients, while the genotype of the virus could not be identified in 5% of the patients. Finally, in 1% of patients coinfection due to 1a-3a genotypes was identified. Conclusion: The dominant genotype of HCV in Bushehr province, Iran, was determined as 1a.